Consumer understanding and evaluation of carbon-neutral electric vehicle charging services. (1st May 2022) - Will, Christian; Lehmann, Nico; Baumgartner, Nora; Feurer, Sven; Jochem, Patrick; Fichtner, Wolf
Highlights: Awareness and preferences for carbon–neutral charging services for electric vehicles. Adaptive Choice-based Conjoint Analysis on survey of 510 consumers in Germany. Of 5 service attributes consumers are most aware of Energy Source, Regionality, Price. Additionality and Balancing Period could offer benefits to the energy system. Last two are less tangible and therefore invoke lower awareness, importance and WTP. Abstract: Electricity from renewable and/or nuclear sources ("carbon–neutral electricity") can be used for charging plug-in electric vehicles in order to significantly reduce their lifecycle carbon emissions. However, little is known about how carbon–neutral charging services (CNCS) for electric vehicles must be designed to attract consumers' interest. Therefore, we conducted a survey including an Adaptive Choice-based Conjoint Analysis to investigate private consumers' awareness and preferences for different service attributes of CNCS, specifically the energy source, regionality of generation, additionality, balancing period, charging flexibility, and price. The online survey in Germany of 510 private consumers who were interested in electric vehicles shows that awareness is highest for the energy source and regionality. Behind price, these are also the second and third most important attributes when choosing a CNCS. Even though, on average, there seems to be a link between the awareness for an attribute, its importance and consumers' willingness to pay, this link proves to be non-significant for individual respondents. In conclusion, providers of CNCS could prominently advertise the attributes consumers are most aware of (i.e., the energy source and regionality of generation). Explaining the less-known, and therefore deemed unimportant, attributes (i.e., additionality, balancing period, and charging flexibility) to consumers could be difficult and costly for providers. From a system perspective, however, more convincing explanation efforts could lead to an increased use of renewables and enhanced system reliability. This raises the challenge for policymakers to create a framework which is both advantageous for the energy system and attractive to consumers. Government-set standards for charging tariffs may be a viable option.